2007
DOI: 10.1007/s10295-006-0200-6
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a maltotriose-producing α-amylase gene from Thermobifida fusca

Abstract: The gene (tfa), encoding a maltotriose-producing alpha-amylase from Thermobifida fusca NTU22, was cloned, sequenced and expressed in Escherichia coli. The gene consists of 1,815 base pairs and encodes a protein of 605 amino acids. The base composition of the tfa coding sequence is 69% G+C and the protein has a predicted pI value of 5.5. The deduced amino acid sequence of the tfa amylase exhibited a high degree of similarity with amylases from Thermomonospora curvata and Streptomyces amylases. The purified amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The plasmid propagation in the expression work was accomplished with E. coli Top 10 (Invitrogen, San Diego, CA). The plasmid pAMY13H8 was constructed with pUC118 and a 3.0-kb BamHI-HindIII inserted fragment, which possessed an amylase gene tfa [10].…”
Section: Microorganisms and Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasmid propagation in the expression work was accomplished with E. coli Top 10 (Invitrogen, San Diego, CA). The plasmid pAMY13H8 was constructed with pUC118 and a 3.0-kb BamHI-HindIII inserted fragment, which possessed an amylase gene tfa [10].…”
Section: Microorganisms and Vectorsmentioning
confidence: 99%
“…C, and the protein has a predicted pI value of 5.5. The deduced amino acid sequence of the tfa amylase exhibited a high degree of similarity with amylases from Thermomonospora curvata and Streptomyces amylases [10].…”
Section: Introductionmentioning
confidence: 99%
“…The base composition of the tfa coding sequence is 69% G ? C and the protein has a predicted pI value of 5.5 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Maltotriose-forming amylases have been reported for S. griseus (Nakakuki et al 1984;Kashiwagi et al 2014), Streptomyces avermitilis (Kashiwagi et al 2014), Bacillus subtilis (Takasaki 1985), Microbacterium imperiale (Takasaki et al 1991;Wu et al 2014), Natronococcus sp. Ah-36 (Kobayashi et al 1992), Thermobifida fusca (Yang and Liu 2004;Yang and Liu 2007), and Microbulbifer thermotolerans (Lee et al 2014), although few maltotrioseforming amylase with an exo-pattern has been found.…”
Section: Introductionmentioning
confidence: 96%